Elementy aksjologii w pismach Ryszarda Legutki i Zdzisława Krasnodębskiego - Pabich, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this paper the author has made an attempt to outline the way Ryszard Legutko and Zdzisław Krasnodębski understand selected values. The views of the aforementioned authors on freedom, tolerance and solidarity were discussed. Freedom is seen as the most characteristic notion of our times, being the key to the understanding of contemporary politics or customs. Tolerance is becoming the ultimate criterion of morality in today’s liberal societies. In turn, the idea of solidarity, as understood by Polish social movement of 1980–1981, seems to be the only concept created in Poland in the last decades which found its place in international circulation of ideas.